PENGEMBANGAN KREATIVITAS MELALUI PEMBUATAN TAS ETNIK TURBAN 3D DENGAN MENGGUNAKAN KAIN TENUN SUMUT DI FLOCHIC HANDMADE - Tanjung, Nurhayati; Anggraini, Yudhistira; Dewi, Eka Rahma; Erni, Erni; Pakpahan, Dermawan; Bahri, Halimul; Damanik, Ulfa Annida; Nitami, Dita Dwi (UPPM Politeknik Gorontalo, 2025)
The development of the tourism industry provides a great opportunity for the community to innovate tourism products that have regional characteristics. However, in reality, there are still many micro industries that do not develop their creativity in creating products that have high selling power, this can be seen from the many tourism products (souvenirs) sold that have similarities between one industry and another and the production of products that use machines rather than handmade makes the products look cheaper. In fact, tourism products should have uniqueness, a good production system (handmade) and product characteristics that characterize a particular region. Many tourism products can be developed into one of the superior products of the region, one of which is a bag product. The goal is to increase creativity through the manufacture of 3D ethnic turban bags using SUMUT woven fabrics at Flochic Handmade. The solutions offered are (1) Training in making 3D ethnic turban bags using SUMUT woven fabrics; (2) Training in sewing bags using interfacing. The activities carried out include preparation, implementation, monitoring and evaluation in the form of counseling and training in making 3D ethnic turban bags. The activities are in the form of strengthening skills through the technique of making 3D ethnic turban bags, selecting raw materials for bags, making bag patterns, sewing techniques, quality control, packaging and online marketing. This activity produces products in the form of 3D ethnic turban bags using North Sumatra weaving.